Patriotic Sities in the Space of a European Metropolis at the Turn of the 21st Century: The Example of Warsaw - Stawarz, Andrzej (Lidé města, 2007)
This article looks at the possibility of undertaking more comprehensive research into the functioning and meaning of cultural patriotic sites in large cities. It takes the example of the largest Polish metropolis – Warsaw – in the period from the birth of the 3rd Republic of Poland to the beginning of the 21st century. It considers a patriotic site a site commemorating a historic event of importance to independence, a site symbolising an armed act, or a site immortalising the act or acts of a specific hero or group of heroes. The study is not aimed at conducting a comprehensive analysis of the spatial arrangement of patriotic sites within the Warsaw cultural scenery, but in this case it analyses the problem of historic remembrance and shaping historic sites.